2003
DOI: 10.1093/ndt/gfg171
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of hypotension-prone haemodialysis patients: is there a critical relative blood volume?

Abstract: An individual RBV limit exists for nearly all patients. In most IME-prone patients, these RBV values were stable with only narrow variability, thus making it a useful indicator to mark the individual window of haemodynamic instabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(100 citation statements)
references
References 11 publications
4
89
0
3
Order By: Relevance
“…Our study has revealed the high frequency of acute HD complications in ESRD patients on two weekly 4-hour HD sessions, some which were fatal. These complications, with profiles similar to those reported elsewhere 18,19 . were more likely to occur during nighttime dialysis when centers were particularly understaffed, and were determined by a combination of both patient-related and health service-related factors.…”
Section: Discussionsupporting
confidence: 89%
“…Our study has revealed the high frequency of acute HD complications in ESRD patients on two weekly 4-hour HD sessions, some which were fatal. These complications, with profiles similar to those reported elsewhere 18,19 . were more likely to occur during nighttime dialysis when centers were particularly understaffed, and were determined by a combination of both patient-related and health service-related factors.…”
Section: Discussionsupporting
confidence: 89%
“…Large-volume ultrafiltration was only weakly associated with intradialytic hypotension in our analysis, which is consistent with a previous study that demonstrated no correlation between the reduction in relative plasma volume and intradialytic hypotension. 18 The development of intradialytic hypotension is a complex process that depends on more than just the volume of ultrafiltration because susceptible patients may have an individualized threshold ultrafiltration volume 19 in addition to other factors such as impaired arteriolar tone, left ventricular dysfunction, and autonomic instability. 20 -22 We did not show a significant association of sex, current smoking, or diabetes mellitus on the relative rates of access thrombosis, consistent with several previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The original aim of RPV monitors was to prevent intradialytic hypotension and related morbid events [107]. Various studies however have shown diverging results [108,109,110,111], even higher mortality and hospitalizations with the use of this technique [111]. …”
Section: Methods Of Dry Weight Assessment: An Overviewmentioning
confidence: 99%